A century of Darwin - Barnett, S. A. (Heinemann, 1958)
Conteúdo: Waddington, C. H. Theories of evolution. Dobzhansky, T. Species after Darwin. Michie, D. The third stage in genetics. Hammond, J. Darwin and breeding. Crowson, R. A. Darwin and classification. Romer, A. S. Darwin and the fossil record. de Beer, G. Darwin and embryology. Clark, W. Le gros. the study of man's descent. Barnett, S. A. The "expression of the emotions". Smith, J. M. Sexual selection. Yonge, C. M. Darwin and coral reefs. Heslop-Harrison, J. Darwin as a botanist. Mac Rae, D. Darwinism and the fossil social sciences. Thoday, J. M. Natural selection and biological progress. Raphael, D. D. Darwinism and ethics.